Elevated Temperature Performance of Expanded Perlite Aggregate Cement Mortar as a Protective Cover for Concrete - K, Purandara.; Scholar, Research; Udayakumar G Professor, Dr; Gopinatha Nayak Assosiate Professor, Dr (International Journal of Engineering and Technology, 2018)
This Paper reports the effect of elevated temperature performance of concrete specimen cube of   sizes 100mm x 100mm x100mm coated with 10 mm thickness of mortar shield made of in the  proportion 1:3 sand and  cement (SC), sand cement and GGBS (SCG), sand, cement and flyash (SCF), expanded perlite aggregates, cement (PC), expanded perlite aggregates, cement and GGBS (PCG), expanded perlite aggregates, cement and flyash (PCF) were subjected varying temperatures of from 200°C to 800°C for 2hour. After specimen were cooled to room temperature in the furnance. The compressive strength were determined. The test results showed that replacement of sand with expanded perlite aggregates acts as a good thermal barrier and protect the structural concrete.